APLIKASI CLIENT-SERVER UNTUK SISTEM INFORMASI KEPUSTAKAAN PADA PERPUSTAKAAN PEGADILAN NEGERI SIDIKALANG - Ronald Fernando Hutasoit; Marlince Novita Karoseri Nababan (Politeknik Bisnis Indonesia, 2021)
This study aims to solve the problem of processing book data at the Sidikalang District Court Library, which currently does not have an information system to process library data such as book data, library member data, borrowing and returning books. In the absence of information regarding available books, the library leader, namely customer representative recreation, the Sidikalang District Court does not know exactly the type and number of books available so that it can hamper the development of the library. This problem is resolved by designing a client-server application for library information systems in libraries. Sidikalang District Court. With this library information system it is hoped that it can simplify the work of librarians, the system for recording book data and member data becomes more structured, fast and accurate, accelerates the process of searching for member data, book data, borrowing, and returning transaction data, and services to library members become more good.